University in the social space - Sztompka, Piotr (Journal of Public Governance, 2016)
The author claims that universities, unlike vocational schools, have a mission to offer general knowledge to their students, also in the domain of the humanities, and to form enlightened citizens rather than skilled workers only. Emphasis on practical skills, narrow specialization, focus on professionalization in all higher education establishments brings about the crisis of the university and atrophy of civil society which is an indispensable element of a well-functioning democracy.